2019
DOI: 10.4014/jmb.1904.04026
|View full text |Cite
|
Sign up to set email alerts
|

Induced Tolerance to Salinity Stress by Halotolerant Bacteria Bacillus aryabhattai H19-1 and B. mesonae H20-5 in Tomato Plants

Abstract: Salinity is one of the major abiotic stresses that cause reduction of plant growth and crop productivity. It has been reported that plant growth-promoting bacteria (PGPB) could confer abiotic stress tolerance to plants. In a previous study, we screened bacterial strains capable of enhancing plant health under abiotic stresses and identified these strains based on 16s rRNA sequencing analysis. In this study, we investigated the effects of two selected strains, Bacillus aryabhattai H19-1 and B. mesonae H20-5, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 66 publications
2
29
0
1
Order By: Relevance
“…ABA is a key phytohormone known to regulate the stress responses, therefore, the ABA biosynthesis genes, viz. NCED1 ( 9‐cisepoxycarotenoid dioxygenase 1 ) and AREB1 ( abscisic acid‐response element‐binding protein 1 ) have been known to modulate the function of stress‐responsive genes and ion transporters, thereby playing an important role in ion homeostasis (Yoo et al, 2019). In this connection, the application of halotolerant bacterial strains like B. aryabhattai H19‐1 and Bacillus mesonae H20‐5 have been shown to stimulate the ABA biosynthesis genes in tomato, thereby improving the performance of the plants under salinity (Yoo et al, 2019).…”
Section: Molecular Mechanism Of Plant Salt‐tolerance Induced By Microorganismsmentioning
confidence: 99%
“…ABA is a key phytohormone known to regulate the stress responses, therefore, the ABA biosynthesis genes, viz. NCED1 ( 9‐cisepoxycarotenoid dioxygenase 1 ) and AREB1 ( abscisic acid‐response element‐binding protein 1 ) have been known to modulate the function of stress‐responsive genes and ion transporters, thereby playing an important role in ion homeostasis (Yoo et al, 2019). In this connection, the application of halotolerant bacterial strains like B. aryabhattai H19‐1 and Bacillus mesonae H20‐5 have been shown to stimulate the ABA biosynthesis genes in tomato, thereby improving the performance of the plants under salinity (Yoo et al, 2019).…”
Section: Molecular Mechanism Of Plant Salt‐tolerance Induced By Microorganismsmentioning
confidence: 99%
“…How plant-associated microbes modulate host physiology to withstand stress conditions is a topic of interest. Recently, some attempts have been made to understand plant responses to salt stress with microbial inoculation, and these suggest the involvement of antioxidative machinery, osmolyte accumulation, and phytohormone signaling (Cao et al, 2017;Chanratana et al, 2019;Orozco-Mosqueda et al, 2019;Vimal et al, 2019;Yoo et al, 2019). However, targeting a single response and single plant tissue will miss the broader effect of plant-microbe interaction and also limit our understanding of stress signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Under salinity stress condition, lettuce seeds inoculated with Azospirillum showed better seed germination and vegetative growth (Barassi et al, 2006). Tolerance to salinity stress has been exhibited by two bacterial strains, Bacillus aryabhattai H19-1 and Bacillus mesonae H20-5 in tomato plants by enhancing ABA levels, accumulating significant levels of proline, abscisic acid (ABA), and antioxidant enzyme activities which might be attributed by the up-regulation of 9-cisepoxycarotenoid dioxygenase 1 (NCED1) and abscisic acid-response element-binding proteins 1 (AREB1) genes (Yoo et al, 2019). Qiyuan et al (2016) have reported that the rhizobacterium Variovorax paradoxus 5C-2 mitigated salinity stress in pea plants by the secretion of 1-aminocyclopropane-1carboxylase (ACC) deaminase, which helped in improving water relations, ion homeostasis, reduced ethylene production and photosynthesis.…”
Section: Plant Growth-promoting Rhizobacteria (Pgpr)mentioning
confidence: 99%